Pengaruh Model Pembelajaran Discovery Learning Berbantuan Media Question Card Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas V SD Negeri 32 Cakranegara - Husnul Amalia, Putri; Syarifuddin; Muhammad Sobri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the application of the Discovery Learning learning model assisted by Question Card media on student learning outcomes in IPAS class V SD Negeri 32 Cakranegara. This study used a quantitative approach with an experimental method involving two groups, namely the experimental class and the control class. The research subjects amounted to 70 students, consisting of 35 VA class students as the experimental class and 35 VB class students as the control class. Data collection techniques were carried out through observations. The results of the hypothesis test which shows that the t value of 5.481 > t table value of 1.667 with a significance value (2-tailed) of 0.000, where 0.000 < 0.05, which means that there is a significant difference between student learning outcomes in the experimental and control classes. The average posttest score of experimental class students is higher than the control class, thus indicating that learning with the Discovery Learning model assisted by Question Card media is more effective than conventional learning. Thus, it can be concluded that the Discovery Learning model assisted by Question Card media has a positive and significant effect on the learning outcomes of IPAS students in grade V of SD Negeri 32 Cakranegara. Keywords: discovery learning, question card, elementary school